Advances in High-Field Magnetic Resonance Spectroscopy in Alzheimer’s Disease - Zhang, Ningnannan; Song, Xiaowei; Bartha, Robert; Beyea, Steven; D’Arcy, Ryan; Zhang, Yunting; Rockwood, Kenneth (Current Alzheimer Research, 2014)
Alzheimer’s disease (AD) affects several important molecules in brain metabolism. The resulting neurochemical changes can be quantified non-invasively in localized brain regions using in vivo single-voxel proton magnetic resonance spectroscopy (SV 1H MRS). Although the often heralded diagnostic potential of MRS in AD largely remains unfulfilled, more recent use of high magnetic fields has led to significantly improved signal-to-noise ratios and spectral resolutions, thereby allowing clinical applications with increased measurement reliability. The present article provides a comprehensive review of SV 1H MRS studies on AD at high magnetic fields (3.0 Tesla and above). This review suggests that patterned regional differences and longitudinal alterations in several neurometabolites are associated with clinically established AD. Changes in multiple metabolites are identifiable even at early stages of AD development. By combining information of neurochemicals in different brain regions revealing either pathological or compensatory changes, high field MRS can be evaluated in AD diagnosis and in the detection of treatment effects. To achieve this, standardization of data acquisition and analytical approaches is needed.
Keywords: brain